Influence of solvent evaporation temperature on the performance of ternary solid polymer electrolytes based on poly(vinylidene fluoride-co-hexafluoropropylene) combining an ionic liquid and a zeolite - Barbosa, João C. (2023)
Solid polymer electrolytes (SPEs) will allow improving safety and durability in next-generation solid-state lithium-ion batteries (LIBs). Within the SPE class, ternary composites are a suitable approach as they provide high room-temperature ionic conductivity and excellent cycling and electrochemical stability. In this work, ternary SPEs based on poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) as a polymer host, clinoptilolite (CPT) zeolite, and 1-butyl-3-methylimidazolium thiocyanate ([Bmim][SCN])) ionic liquid (IL) as fillers were produced by solvent evaporation at different temperatures (room temperature, 80, 120, and 160 °C). Solvent evaporation temperature affects the morphology, degree of crystallinity, and mechanical properties of the samples as well as the ionic conductivity and lithium transference number. The highest ionic conductivity (1.2 × 10-4 S·cm-1) and lithium transference number (0.66) have been obtained for the SPE prepared at room temperature and 160 °C, respectively. Charge-discharge battery tests show the highest value of discharge capacity of 149 and 136 mAh·g-1 at C/10 and C/2 rates, respectively, for the SPE prepared at 160 °C. We conclude that the fine control of the solvent evaporation temperature during the preparation of the SPE allows us to optimize solid-state battery performance.